Molecular cloning of a family of retroviral sequences found in chimpanzee but not human DNA. - Bonner, T I (1982)
A number of retrovirus-like sequences have been cloned from chimpanzee DNA which constitute the chimpanzee homologs of the endogenous colobus type C virus CPC-1. One of the clones contains a nearly complete viral genome, but others have sustained deletions of 1 to 2 kilobases in the polymerase gene. The pattern of related sequences detected in other primate species is consistent with the genetic transmission of these sequences for millions of years. However, the appropriately related sequences have not been detected in human, gibbon, or orangutan DNAs. These results suggest either that this family of sequences has been deleted from humans, gibbons, and orangutans, or that the genes were recently acquired in the chimpanzee and gorilla lineages.